Factors inhibiting the adoption of industrial revolution 4.0 in Malaysian construction industry - Qasem Almatari, Husam Abdullah; Chan, Melissa; Masrom, Md Asrul Nasid (2024)
Purpose – The construction industry is a major economic driver in Malaysia, playing a pivotal role in the developing nations economic growth. Malaysia’s reliance on labor-driven construction practices often sees local industry lagging in adopting technological advancements common to the construction sector on a global scale. This study investigates the challenges faced by project players in using new construction industrial revolution (IR) 4.0 technologies and the difficulties in implementing these technologies in construction projects. Design/methodology/approach – A quantitative survey was distributed to 183 practitioners in the Malaysian construction industry. The collected data (N 5 121) has been analyzed using statistical software to calculate relative importance index values for the identified factors. A triangulation approach to validate the factors obtained from the survey was conducted with an expert group to ensure there were no additional considerations identified in the study. Findings – The study results show that the main factors in adopting construction IR 4.0 technologies are 1) high implementation costs, 2) hesitation to adopt technologies, 3) lack of standards, 4) legal and contractual uncertainty and 5) complexity. By investigating these factors, cost and regulation issues can gradually be resolved, with construction firms implementing new technologies, educating workers and ensuring government involvement in training for skill development to support IR 4.0. Originality/value – The outcome of these efforts to resolve construction productivity would be beneficial in their industry impact on practice and digital transformation. Additionally, the results add to the body of knowledge for construction practitioners and technology developers to work together efficiently on the implementation of construction 4.0 technologies.